m(5-x)=7-y

Divide each term in m(5-x)=7-y by m.

m(5-x)m=7m+-ym

Cancel the common factor of m.

Cancel the common factor.

m(5-x)m=7m+-ym

Divide 5-x by 1.

5-x=7m+-ym

5-x=7m+-ym

Move the negative in front of the fraction.

5-x=7m-ym

5-x=7m-ym

Subtract 5 from both sides of the equation.

-x=7m-ym-5

Multiply each term in -x=7m-ym-5 by -1.

(-x)⋅-1=7m⋅-1-ym⋅-1+(-5)⋅-1

Multiply (-x)⋅-1.

Multiply -1 by -1.

1x=7m⋅-1-ym⋅-1+(-5)⋅-1

Multiply x by 1.

x=7m⋅-1-ym⋅-1+(-5)⋅-1

x=7m⋅-1-ym⋅-1+(-5)⋅-1

Simplify each term.

Multiply 7m⋅-1.

Combine 7m and -1.

x=7⋅-1m-ym⋅-1+(-5)⋅-1

Multiply 7 by -1.

x=-7m-ym⋅-1+(-5)⋅-1

x=-7m-ym⋅-1+(-5)⋅-1

Move the negative in front of the fraction.

x=-7m-ym⋅-1+(-5)⋅-1

Multiply -ym⋅-1.

Multiply -1 by -1.

x=-7m+1ym+(-5)⋅-1

Multiply ym by 1.

x=-7m+ym+(-5)⋅-1

x=-7m+ym+(-5)⋅-1

Multiply -5 by -1.

x=-7m+ym+5

x=-7m+ym+5

x=-7m+ym+5

Solve for x m(5-x)=7-y